Heat of hydration of Portland high-calcium fly ash cement incorporating limestone powder: Effect of limestone particle size - Pailyn Thongsanitgarn (2018)
This study investigated the limestone powder (LS) particle size effect on the heat of hydration of Portland cement (PC) and high-calcium fly ash (FA) systems. The LS used has a maximum particle size of 5 and 20 μm, respectively. Isothermal calorimetry was used to measure the heat evolution during the hydration process of the cement and PC-FA pastes. The results show the particle size of LS had a significant influence on the observed heat of hydration both on rate of reaction and total amount of heat release. The hydration rates of both PC-LS and PC-FA-LS systems were accelerated by 5 μm LS, while 20 μm LS did not. For PC-FA-LS system, the total heat release at 48 h when using 5 μm LS were higher than FA at 30% replacement level whereas 20 μm LS showed similar total heat release. However, the total heat release of these ternary mixtures with both LS particle sizes was still lower than PC control. X-ray diffraction (XRD) technique and thermogravimetric (TG) analysis were applied to identify the hydration products. XRD results show the formation of carboaluminates and ettringite was still found at 28 days, indicated the stabilization of ettringite when both LS particle size were used. The reaction between LS and PC or FA was confirmed by TG results in the reduction of CaCO3content. © 2014 Elsevier Inc. All rights reserved.